Men's talk in a Lebanese shisha café - Bahous, Rima (2013)
This qualitative study explores the relationship between gender identity and conversational behavior in all-male groups' interactions in a Lebanese context. We collected the data through non-participant observations and interviews with 15 participants in a shisha café, and we examined the verbal and nonverbal behaviors of the men there. Results of the analysis of participants' verbal and nonverbal behaviors clearly indicate that men, in all-male groups, attempt to use different conversational strategies (e.g. politeness strategies) and different nonverbal cues (e.g. laughing, frowning) in order to maintain power relations and establish solidarity within the group. The research findings are substantial since they highlight how men's functions of different conversational styles reflect their powerful status within all-male Lebanese society.